A sophia como télos da pedagogia da razão: reflexões para a educação a partir da atitude filosófica de Platão - Teixeira, Luiz Paulo (2018)
This work aims to contribute to the discussion about the nature and the purpose of education. For this, seek in Plato's philosophy two essential elements that can help to elaborate a consistent problem of research: the philosophical attitude and pedagogy of reason elaborated of the Athenian philosopher-educator. The question arises as follows: "in which the philosophical attitude and pedagogy of Plato's reason can contribute to the discussion in education?". In this wake, it is proposed as a general objective "to do research the philosophical attitude and the pedagogy of reason and to perceive in them some fundamental elements to understand the essence and the purpose of education in these times calleds postmoderns, in which the man isolates himself, refutes the notion of objective truth and shows clear disinterest on the affairs of the city". The data collection and the thematic analysis have enabled to conclude that sophia is the télos of the pedagogy of reason and that Plato's philosophical attitude is important in reflecting on education in these times of irrationality. This proposition arises from a way built through the analysis of Plato's existence as an educator and historical events that led him to formulate an educational problem. Then, we seek to properly conceptualize the pedagogy of reason and its search for timelessness in relation to good. Finally, we try to perceive the consequences of these reflections for these times in which irrational theoretical, behavioral and political positions find in the set of ideas "post" a fertile soil to strengthen. Education is then proposed as conversion to the structuring forms of goodness / beauty, justice and truth: fundamental concepts for structuring and preserving life (sophia). The research developed here is of a theoretical nature and structured according to the rigor, criticality and overall vision proper to the philosophically reflexive and dialectical approaches.